De dødes flækker – Slidsporsanalyse af flækker fra et megalitanlæg og en boplads - Skriver, Claus (Kuml, 2011)
Blades of the dead Use-wear analysis of blades from a megalithic monument and a settlement In discussions concerning the significance of re-burials in megalithic tombs and the broader religious ideology associated with the re-use of megalithic monuments, interpretations have often focussed on the forecourt, the area in front of the monument with so-called sacrificial or offer deposits, and analyses of skeletal material. In this article, some suggestions are made with respect to the ritual use of megalithic tombs, based primarily on use-wear analysis of the blades recovered from just such a monument at Damsbo Mark on SW Funen (fig. 1). A settlement blade assemblage from the site of Süssau in Northern Germany has been employed for comparison. In addition to use-wear analysis, the investigations have also comprised measurements of edge angle, length-width-thickness of the blades, counting of pieces showing retouch and cortex as well as attribute analysis in relation to an interpretation of the degree to which the blades were manufactured using hard or soft technique. The megalithic monument at Damsbo Mark The monument is located on SW Funen, c. 3 km SE of the Sarup locality - renowned for its Neolithic causewayed enclosures. The pottery dates the re-burials in the monument to period III/V of the Funnel Beaker culture. It cannot be determined whether all the blades originate from the Funnel Beaker culture or whether they could be artefacts associated with potentially later burials. Use-wear analysis could be conducted on 27 of the 48 blades. The most commonly worked material was hide/cooked meat, followed by bone and meat, bone/antler, cereals and the material which produces polish 23. On four of the blades, the contact material could not be identified and two of the blades are interpreted as unused (fig. 2). The most common mode of use was by cutting (fig. 3). A selection of the analysed tools is shown in figure 4. The Süssau settlement The settlement was excavated by Dr Jürgen Hoika in 1965-67. The site is dated to period III/IV of the Funnel Beaker culture. A total of 65 blades were selected for the present analysis and it proved possible to analyse 28 of these. The most commonly worked material was bone/antler, boneand meat, wood and cereal; the blades had also been used for slaughtering animals (fig. 5). The most common mode of working was cutting and slicing (fig. 6). A selection of the analysed tools is shown in figure 7. Comparison of the blades from Damsbo and Süssau The analysis revealed some similarities but also great differences between the blades from Damsbo and Süssau. For example, rather more than a third of the blade assemblage from Damsbo is fragmented whereas at Süssau this proportion is almost half. This situation, together with number of blades retaining cortex and those showing retouch, underlines the fact that these assemblages represent two rather different contexts. Identification of the contact materials for the blades from the two sites has produced surprising results. Traces arising from the working of hide/skin and the material that creates polish 23 were not found on the settlement blades, while evidence for the working of wood was not apparent on the blades from the tomb. The appearance of the blades from the two sites differs markedly; the immediate impression gained is that those from the megalithic tomb are long, slender and carefully made in contrast to the blades from the settlement (figs. 16-17). Median measurements support this visual impression (figs. 8-13). Attribute analysis indicates that there could be a difference in the manufacturing technique employed for the two blade assemblages. The blades from the megalithic monument have several attributes indicating soft manufacturing technique (figs. 14-15). Interpretation Through these differences it is apparent that the settlement material represents more everyday tasks, while that from the megalithic monument represents religious activities, or activities associated with treatment of the dead. The long blades could possibly have been part of the personal equipment, which accompanied the corpse into the grave, or perhaps they were specially manufactured or chosen for religious purposes in connection with interment. During periods MN III-V, megalithic monuments were used for repeated bone depositions. However, the number of blades present is not determined by the number of dead. For example, a megalithic tomb was found to contain the bones of 22 individuals but only two blades. Furthermore, the individuals placed in megalithic monuments have been disarticulated; a complete articulated skeleton has never been encountered in this context. Some researchers believe that this arises from the rough-handed clearing out of the chamber in advance of new burials. Others have pointed out that, if this is correct, the final grave should be intact. This has lead to a hypothesis that the dismemberment of the skeletons was intentional and was associated with ritual activities. With time, this hypothesis has become the most widely accepted. Ritual depositions are also encountered outside megalithic monuments. Here there are flint axes and chisels, often showing clear signs of intentional damage and destruction. It is obvious that the entire megalithic monument constituted the background for extensive activities which, in some respects, showed strongly destructive traits. Some researchers believe that the chaos evident in and around megalithic monuments represents intentional acts which had the purpose of destroying both the individual and their identity. How do the blades placed in the grave fit into the picture outlined above? The analyses show that most of the blades have been used and that those that have not are much shorter than the common median. The blades have been used on specific materials such as bone/antler, bone/meat, hides/cooked meat, cereals and the material which produces polish 23, i.e. a broad spectrum which, with the exception of hides/cooked meat, is also represented at the settlement. It is striking that none of the tools has been used on wood; this must have been a conscious decision. Furthermore, the attribute analysis indicates that the blades could have been made using a special manufacturing technique. If they were manufactured for a specific individual then there is an immediate divergence between attempting to destroy an individual’s identity, on the one hand, while at the same time placing an individual’s personal effects in the grave, on the other. It is possible that the blades were used in dismembering individuals prior to the skeletal parts being placed in megalithic tombs together with the blades. Cut marks on human bones dating from this time reveal that human flesh was cut/butchered/dismembered. If the corpse had lain for some time and had been allowed to dry out, it is possible that this dismemberment could produce use-wear resembling that from working in dry hide/skin. This hypothesis does not, however, explain the presence of tools showing evidence of having been used on cereals and the material which produces polish 23. The blades can also be interpreted as representing a religious deposition of grave goods as a symbol of the tasks which are expected after death. It is likely that blades for this purpose would have been specially chosen or manufactured, as seen for example with certain types of pottery vessel. This interpretation could explain the presence of sickle blades and the blades with polish 23. The absence of tools which have been used on wood could be the result of this function having been performed by the axes and chisels which were also present. The use of megalithic monuments during this period reveals two forms of offering: one external, comprising broken or damaged flint artefacts, and the other internal, involving intact artefacts. The latter contrasts starkly with the pronounced destructive traits seen in the actual burials and offerings on the forecourt. If the blades inside the megalithic monuments were manufactured using a different technique, as indicated by the attribute analysis, a fascinating picture emerges of a culture mastering two flint-working techniques: one used primarily for the production of tools on the settlement and another employed specifically for sacral purposes. It is clear that the deposition of the blades can be interpreted as having several instigators. The results of the analyses indicate that our perception of artefacts in megalithic monuments should be taken up to revision. Instead of interpreting these as personal grave goods, they should be perceived as offerings – not to a specific individual whose identity has been erased by the disarticulation of their bones but to the dead as a group, or, conversely, as tools employed in a ritual fashion in connection with dismemberment. Claus Skriver Moesgård Museum